Ideal body weight: A commentary. (December 2021) - Chichester, Sierra; Holmes, Tara M.; Hubbard, Jane
Summary: Background & aims: The Ideal Body Weight (IBW) model has provided dietitians and researchers with a quick method of risk assessment but is known to be imperfect. IBW formulas were developed from anthropometric measurements of life-insurance policy holders obtained between 1885 and 1908, providing statistics of mortality, organized by sex and age. Actuaries of the U.S. life insurance companies published data on the impact of overweight/obese status and mortality risk. Research of the same era repeatedly revealed either no significance or an inverse relationship. The intent of this text is to draw attention to the complexity and overall discussion of utility of the IBW method. Methods: Reviewed relevant literature from the development of IBW through the recent findings in 2014. Results: Height, weight, and frame fail to consider comorbidities and genetics. IBW formulas assume that weight increases as a linear function of height. Weight has been shown to increase not just as a function of height, but also of volume: body width, trunk length, and musculature. Depending on standards of practice, several equations may be used. Conclusions: The IBW model is utilized but not limited to creating enteral and parenteral feeding plans, avoiding malnutrition, aiding weight management, identifying transplant eligibility, and determining inclusion or exclusion from research studies. Socially, the significance around "ideal" can impact a weight-centric mentality and negatively affect a large portion of the population. Every individual has a distinct "ideal" body weight based on genetics, environment and lifestyle, which could be represented and assessed effectively with new tools.